New records of Ichneumonidae (Hymenoptera: Ichneumonoidea) from Mexico - González–Moreno, Alejandra; Bordera, Santiago (Zootaxa, 2011)
A total of 55 first records of Ichneumonidae are reported from Mexico, raising the total number of known species from Mexico to 1,115. Two genera, Picrostigeus and Paraphylax, are reported for the first time from the Neotropical Region. Material was collected over a one year period by Malaise traps in three habitats; dry forest, savannah and coastal dune scrubland in the Ria Lagartos Biosphere Reserve, Yucatán, Southeast Mexico. A total of 1,302 individuals of Ichneumonidae are included in this paper. 45 species (81%) of the new records have a Neotropical distribution; seven species (12%) have been reported previously only from the Nearctic; and one species (2%) are recorded from both the Nearctic and Neotropical regions. Most species have a higher abundance in the rainy season, and the dry forest habitat provided more new records than the other habitats.